What Consumers Are Looking for in Strawberries: Implications from Market Segmentation Analysis. Issue 1 (12th July 2016) - Wang, Jingjing; Yue, Chengyan; Gallardo, Karina; McCracken, Vicki; Luby, James; McFerson, Jim
ABSTRACT: An online choice experiment was conducted to investigate U.S. consumer preferences for attributes of fresh market strawberry fruit. Using a latent class logit model, three different groups of consumers are identified: "Balanced Consumers, " "Experience Attribute Sensitive Consumers, " and "Search Attribute Sensitive Consumers." This information on consumer segmentation can help the fresh market strawberry industry identify target markets, and provides valuable information to breeders, growers, and retailers to prioritize fruit attributes in their breeding, growing, or product sourcing decisions.